Sulfur Preparation and New Measures of Control against Various Vine Diseases - Khojievich, Tokhtaev Shonazar (American Journal of Biodiversity, 2024)
Currently, in the work that is being carried out in our country to increase vineyards, instead of harmful chemicals, it is appropriate to use biological control methods and harmless substances. In the first place, it is advisable to use sulfur-containing preparations in order to protect vineyards from harmful organisms. Our scientists and farmers have been using various forms of sulfur against grape dew, anthracosis and other diseases for several centuries. We are now in compliance with the preparation of new preparations of sulfur using the residues of petroleum products, this information is presented in our following works. Is a fight against the disease. Because when affected by the disease of oidum, on average, 20-30% of the crop is lost. To prevent this, it is appropriate to use the new SFM substance.